Study on the photosynthetic growth characters in Cimicifuga dahurica (Turcz.) Maxim under different supplemental light environments - Xie, Sheng-Nan (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024. Published by Elsevier Masson SAS.